The osteocyte: master directors of bone remodelling, mineralisation and phosphate-calcium homeostasis - Khalid, Kamarul Ariffin; Findlay, David M; Atkins, Gerald J (2019)
Traditionally, the curriculum in medical schools does not emphasise osteocytes and they are usually relegated to being ‘osteoblasts that got trapped in bone lying dormant’. Even higher training does not put much emphasis on osteocytes or keep up with the latest publications on them. Thus, many medical professionals are still not aware of the myriad roles that osteocytes play in maintaining bone in a normal environment or their involvement in many clinical diseases that affect bone. Osteocytes are the most abundant cell type to be found in bone but they are the least investigated due to two factors. Firstly, osteocytes were thought to be rather inert cells that contribute little to bone maintenance. This has been proven wrong in recent years. Secondly, and probably more importantly, is the technical difficulty of extracting osteocytes from their lacunae in bone or to study them in situ. However, in the last decade or two more and more evidence has accumulated to indicate that osteocytes are the key cells in regulating bone remodelling via mechanotransduction and also for the homeostasis of calcium and phosphate. The development of osteocyte-like cell lines and animal models with cell specific gene mutations, together with the evolution of new and better techniques for isolating and culturing osteocytes and characterising them, has helped in fuelling the sudden wealth of new knowledge on osteocyte biology. A major cell signalling protein for the regulation of bone remodelling is sclerostin. Mature osteocytes are the main source of sclerostin, which is found to reduce bone formation and negatively regulate osteoblast differentiation via the Wnt/β-catenin pathway. Recent evidence suggests that sclerostin also promotes osteoclast formation by regulation of the receptor activator of nuclear factor kappa B (RANKL)-osteoprotegerin (OPG) axis. Sclerostin production is suppressed when bone is mechanically loaded. These findings point to the central role of osteocytes in bone remodelling. Fibroblast growth factor-23 (FGF23) is also expressed by mature osteocytes predominantly and seems to regulate phosphate and 1,25(OH)2vitD3 levels. Phosphate homeostasis is known to be associated with DMP1, which regulates FGF23 production. FGF23, together with its co-receptor the Klotho protein, not only plays a role in matrix mineralisation but also decreases phosphate reabsorption and inhibits 25(OH)vitD3 conversion to 1,25(OH)2vitD3 in the kidneys, making bone another endocrine organ. Klotho gene deleted mice have a disturbed spatial distribution of osteocytes and synthesis of bone matrix proteins together with the prematurely-aged appearance of its bone cells. It is now known that klotho deficient mice die prematurely due to tissue calcification brought about by very high levels of phosphate and 1,25(OH)2vitD3. In conclusion, osteocytes are very dynamic cells that are the key regulators of not only bone health but also phosphate and calcium homeostasis.